Adhered macrophages as an additional marker of cardiomyocyte injury in biopsies of patients with dilated cardiomyopathy - Warmusz Oliwia; Badziński Arkadiusz; Reichman-Warmusz Edyta; Dudek Damian; Wojnicz Romuald (Open Medicine)
Macrophage accumulation found in biopsy specimens of patients with dilated cardiomyopathy (DCM) has been thought to reflect chronic myocarditis. However, it is unsettled whether they are responsible for the active or persistent phase of the disease.